2004
DOI: 10.1021/bp0342755
|View full text |Cite
|
Sign up to set email alerts
|

Serial 13C-Based Flux Analysis of an L-Phenylalanine-Producing E. coli Strain Using the Sensor Reactor

Abstract: With the aid of the recently developed Sensor reactor system, a series of three subsequent (13)C labeling experiments was performed mirroring the l-phenylalanine (l-Phe) production phase of a recombinant E. coli strain that was cultivated under industry-like conditions in a 300 L bioreactor. On the basis of the data from NMR labeling analysis, three subsequent flux patterns were successfully derived monitoring the l-Phe formation during an observation window from 14 to 23.3 h process time. Linear programming w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The predominating industrial process conditions are batch and fed-batch. It has been shown in several studies that 13 C-MFA can be applied under these conditions (Costenoble et al, 2007;Drysch et al, 2004;Fischer et al, 2004;Iwatani et al, 2007;Wahl et al, 2004;Wittmann and Heinzle, 2002). 3.…”
Section: Choice Of Experimental Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominating industrial process conditions are batch and fed-batch. It has been shown in several studies that 13 C-MFA can be applied under these conditions (Costenoble et al, 2007;Drysch et al, 2004;Fischer et al, 2004;Iwatani et al, 2007;Wahl et al, 2004;Wittmann and Heinzle, 2002). 3.…”
Section: Choice Of Experimental Frameworkmentioning
confidence: 99%
“…Analytical equipment. In principle, labeling information can be provided by measuring isotopic patterns of proteinogenic amino acids or metabolic intermediates using NMR Marx et al, 1996;Sauer et al, 1997;Wahl et al, 2004) or MS devices (Antoniewicz et al, 2007a;Fischer et al, 2004;Huege et al, 2007;van Winden et al, 2005;. When applying the isotopically non-stationary approach measurements from low concentrated intermediates (including labeling fractions and pool sizes, cf.…”
Section: Choice Of Experimental Frameworkmentioning
confidence: 99%
“…Phenylalanine, for example is used for the production of the sweetener, Aspartame. Wahl et al (2004) conducted a series of three subsequent labeling experiments mirroring the phenylalanine production phase of E. coli grown under industry-like conditions in a 300 l reactor. The large flux from PEP to pyruvate was suggested to be responsible for the decrease in phenylalanine yield, since PEP is a pathway precursor for phenylalanine, and that PEP synthase was an ideal target for overexpression.…”
Section: Phenylalaninementioning
confidence: 99%
“…The product of this gene, carbon storage regulator protein, binds several species of mRNA molecules responsible for carbon metabolism, specifically repressing pckA and pps (encoding phosphoenolpyruvate carboxykinase and phosphoenolpyruvate synthase), thus inhibiting the formation of phosphoenolpyruvate, an essential precursor of aromatic amino acid biosynthesis. Not surprisingly, an independent study reported increased titers for phenylalanine in E. coli strains in which the pps gene was overexpressed due to increased phosphoenolpyruvate availability (227). Similarly, disrupting three repressors of galactose uptake (Gal6p, Gal80p, and Mig1p) in S. cerevisiae increased galactose consumption (161).…”
Section: Disparity In Gene Expression and Metabolic Fluxmentioning
confidence: 99%